Mediating Effect of Creative Self-Efficacy in the Relationship between Knowledge Sharing and Perceived Organizational Support - Ahmad, Afan; Achmad, Gusti Noorlitaria; Adhimursandi, Doddy (International Journal of Multidisciplinary Approach Research and Science, 2025)
This study investigates the mediating role of creative self-efficacy in the relationship between knowledge sharing and perceived organizational support on innovative work behavior among academic staff. Drawing upon social cognitive theory, the research explores how individuals' belief in their creative capabilities influences the translation of shared knowledge and organizational support into innovative outcomes. Using a quantitative approach and survey data from university faculty members, the analysis reveals that both knowledge sharing and perceived organizational support significantly predict creative self-efficacy. Furthermore, creative self-efficacy is found to have a strong positive effect on innovative work behavior and partially mediates the influence of knowledge sharing and organizational support. These findings underscore the importance of fostering a supportive environment and enhancing creative confidence to drive innovation within academic institutions. The study offers practical implications for organizational leaders seeking to cultivate innovation through targeted development of creative self-efficacy.